A study on dissociation of sII krypton hydrate and the effect of hydrocarbon guest molecules as stabilizer by molecular dynamics simulation. (2nd November 2017) - Reshadi, Pourya; Modarress, Hamid; Dabir, Bahram; Amjad-Iranagh, Sepideh
ABSTRACT: In this paper, the characteristics of structure II krypton hydrate are studied by molecular dynamics simulation under isobaric-isothermal ( NPT ) ensemble condition. The dissociation process of the hydrate is simulated and the effect of krypton (Kr) and various types of hydrocarbon guest molecules (HGMs) on the stability of the hydrate structure is investigated during the simulation time of 1 ns. The studied HGMs are propane, isobutane, neopentane, cyclopropane, cyclobutane, cyclopentane and cyclopentene. The structural change of the Kr-hydrate is analyzed with the radial distribution function, mean square displacement and diffusion coefficient. As temperature increases, the obtained results indicate a gradual increase in the Kr-hydrate cell size, which leads to distortion of the hydrate lattice and escaping of the encapsulated Kr molecules from the hydrate structure to form small bubbles of Kr aggregated in the aqueous solution.